CHALLENGES OF THE MILITARY NEUTRALITY OF THE REPUBLIC OF SERBIA IN A CHANGED SECURITY ENVIRONMENT - Hatidza, Berisa Alil; Barišić, Igor (The Policy of National Security, 2025)
The war in Ukraine has caused significant changes in the security environment of the Republic of Serbia. Following Russia's military intervention in Ukraine, relations between the West and Russia have reached the level of open political and economic conflict, with the dangerous potential for such a confrontation to escalate into military and nuclear confrontation. Russia has been subjected to unprecedented, comprehensive sanctions. The geopolitical conflict between the West and the Russian Federation has also caused significant changes in the security and defence policies of the European Union and NATO member states, significant increases in their military budgets, the accession of Sweden and Finland to NATO, a historic increase in NATO’s military presence on its eastern borders, and significant military, humanitarian, and financial assistance to Ukraine's war efforts. In the energy sector, the process of energy “De-Russificationˮ of Europe is in its final stages. Smaller European countries still importing Russian oil and gas will be forced to rapidly diversify their supplies to mitigate the potential economic consequences of interrupting Russian oil and gas imports. The war in Ukraine initiated and intensified a tectonic process of political, security, and economic realignment in Europe and the world, as a result of which the military neutrality of the Republic of Serbia was exposed to serious pressure from key international actors to side with one of the parties in the aforementioned conflict. The military neutrality of the Republic of Serbia represents a legitimate security and defense option. However, the uncertainties regarding the legitimacy of the military neutrality of the Republic of Serbia create space for exerting political, security, and economic pressure because this important defense interest is conditioned by the vital national interests of the Republic of Serbia, in particular the aspiration towards membership in the European Union, the preservation of territorial integrity, as well as the preservation of energy security. The war in Ukraine has caused a deterioration in Serbia’s geopolitical position, which has been exploited in the process of aggravating relations and escalating the conflict between Belgrade and Pristina to establish firm political and security control over the territory and the local Serbian population and gradually abolish the remaining elements of Serbian institutions in the north of Kosovo and Metohija. At the same time, the “stabilization” of the situation in Kosovo and Metohija significantly reduces Russia's ability to use the "Kosovo precedent" to justify military intervention in Ukraine. On the other hand, the escalation of the conflict between the West and the Russian Federation in the energy sector seriously threatens Serbia's energy security, as it has limited possibilities to diversify its supply relatively quickly. The recent introduction of sanctions against the company “NIS” represents one of the biggest challenges to the energy security of the Republic of Serbia. However, the persistent refusal to impose sanctions on the Russian Federation may negatively affect Serbia's European and economic prospects, given the level of foreign trade with the European Union. On the other hand, the Republic of Serbia is making obvious efforts to preserve its status of military neutrality by politically balancing between the warring parties. The war in Ukraine is turning into a protracted armed conflict of attrition. In this new, global, and exhausting “war of materials” and the tightening of political, security, and economic relations, the Republic of Serbia will have a challenging and complicated foreign policy position, given its persistent efforts to maintain good relations with the West, but also with the Russian Federation, which is integral to its policy of military neutrality. One of the key problems of the sustainability of Serbia’s military neutrality is its connection with the issues of preserving Kosovo and Metohija and the prospect of membership in the European Union, vital national interests that, in the tense geopolitical circumstances, can hardly be reconciled. On the other hand, any alignment or non-alignment about sanctions against the Russian Federation will have serious consequences, both for resolving the problem of Kosovo and Metohija and for the energy and economic security of the Republic of Serbia. The research methodology is based on the analysis of relevant sources and literature.
Keywords: challenge; sustainability; military neutrality; security environment; war